Assessing the Structure and Environmental Impact of Mangrove Forests in Segara Anakan, Cilacap, Central Java - Wintah; Kiswanto (Akta Agrosia, 2024)
The mangrove ecosystem in Segara Anakan has experienced significant habitat changes, with nearly half of the area damaged, thereby impacting the mangrove vegetation structure. This study determines the structure of mangrove forest communities using a survey method and a random sampling technique. เว็บสล็อต | R4shub Quadrants of varying sizes were used to measure tree, sapling, and seedling vegetation. The study identified 10 mangrove species from 4 families: Rhizophoraceae (5 species), Meliaceae (1 species), Lythraceae (2 species), and Acanthaceae (2 species). Tree-level mangrove density was highest at station 3 (0.28 ind/m²), followed by stations 2 (0.27 ind/m²) and 1 (0.16 ind/m²). Sapling density was also highest at station 3 (13.08 ind/m²), followed by stations 2 (12.48 ind/m²) and 1 (9.84 ind/m²). These findings provide valuable insights into the current state of mangrove ecosystems in Segara Anakan, emphasizing the need for conservation and management efforts to mitigate further habitat degradation and loss of biodiversity.  Keywords: density, environmental impact, mangrove, species richess,